2009
DOI: 10.1021/jf902929h
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics Analysis Reveals the Compositional Differences of Shade Grown Tea (Camellia sinensis L.)

Abstract: The different cultivation methods affect tea quality by altering the basic metabolite profiles. In this study, the metabolome changes were investigated in green tea and shade cultured green tea (tencha) by liquid chromatography-mass spectrometry (LC-MS) and gas chromatography-mass spectrometry (GC-MS) coupled with a multivariate data set. The principal component analysis (PCA) and orthogonal projection to latent structures discriminate analysis (OPLS-DA) of green tea clearly showed higher levels of galloylquin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
142
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 211 publications
(162 citation statements)
references
References 31 publications
6
142
2
Order By: Relevance
“…The homogenate was centrifuged twice for 10 min at 4,000 . The supernatant was collected and used to determine total phenolic content using a colorimetric Folin-Ciocalteu method as previously described by Ku et al [16]. Briefly, 10 L of sample extracts was mixed with 0.2 N Folin-Ciocalteu phenol reagent (100 L) in a 96-well plate.…”
Section: Total Phenolics and Antioxidantmentioning
confidence: 99%
See 1 more Smart Citation
“…The homogenate was centrifuged twice for 10 min at 4,000 . The supernatant was collected and used to determine total phenolic content using a colorimetric Folin-Ciocalteu method as previously described by Ku et al [16]. Briefly, 10 L of sample extracts was mixed with 0.2 N Folin-Ciocalteu phenol reagent (100 L) in a 96-well plate.…”
Section: Total Phenolics and Antioxidantmentioning
confidence: 99%
“…Antioxidant capacity was evaluated using 2,2 -azinobis(3-ethylbenzthiazoline-6-sulfonic acid) (ABTS) and ferric reducing antioxidant power (FRAP) methods according to Ku et al [16]. Briefly, the ABTS method involved dissolving 7 mM ABTS (ammonium salt) in potassium phosphate buffer (pH 7.4) and combining with 2.45 mM potassium persulfate.…”
Section: Total Phenolics and Antioxidantmentioning
confidence: 99%
“…Although polyphenols have many health-promoting effects, the relationship between these compounds and the inhibition of MRLC phosphorylation in human endothelial cells remain unclear. These polyphenols differed from those reported by Ku et al 112,113) Additionally, such polyphenols, especially anthocyanins, were barely detected in the most consumed and distributed Japanese Notes: (A) PCA score plot shows separate clustering of metabolic profiles corresponding to Nou-6 and SR, and other cultivars. The number in the figure indicates the bioactivity ranking of tea cultivars.…”
Section: Evaluation Of Green Tea Functionality On the Basis Of Imentioning
confidence: 60%
“…112,113) They suggested that several polyphenolic compounds were associated with a specific manufacturing type or cultivation method. In contrast, we investigated relationships between metabolomic data and health-promoting effects in 43 green tea cultivars.…”
Section: Evaluation Of Green Tea Functionality On the Basis Of Imentioning
confidence: 99%
“…In this manner, green tea becomes flavor-rich before it is hand-harvested (Hirai et al, 2008). Shading leads to greener, tastier, and less astringent tea leaves and, thereby, attracts the consumer (Ku et al, 2009). After harvest, the young shoots are processed into green tea powder by series of processing steps: steaming; drying; removing of stems, midribs, and veins; and fine stone milling (Tokunaga, 2004).…”
Section: Introductionmentioning
confidence: 99%